SIMULTANEOUS DETERMINATION OF DIPHENHYDRAMINE, EPHEDRINE, NOSCAPINE, AND GLYCEROL GLYCOLATE USING STABILITY-INDICATING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY: APPLICATION TO NOSCOF TABLETS - BHASKARARAO, PULAGURTHA; DANNANA, GOWRI SANKAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Noscof tablet is a fixed dosage combination formulation having diphenhydramine (DH), ephedrine (ED), noscapine (NP), and glycerol glycolate (GG). A sensitive, selective, accurate, precise, and stability-indicating reversed-phase high-performance liquid chromatography (RP-HPLC) method with photodiode array detection has been developed and validated for simultaneous analysis of DH, ED, NP, and GG in bulk drug and Noscof tablets. Methods: Reversed-phase chromatographic separation and analysis of DH, ED, NP, and GG were done on an Altima C18 column with 0.01 M KH2PO4 buffer (pH 3.5) and acetonitrile (50:50%, v/v) as mobile phase at 0.8 ml/min flow rate in isocratic mode. Detection was performed at 260 nm. The method was validated in harmony with International Conference on Harmonization (ICH) guidelines. The tablet sample solution was subjected to diverse stress conditions using ICH strategy such as hydrolytic degradation (neutral - with distilled water, alkaline - with 2 N NaOH, and acidic - with 2 N HCl), oxidation (with 10% H2O2), photodegradation (exposing to UV light), and dry heat degradation (exposing to 105°C). Results: Using the above stated chromatographic conditions, sharp peaks were obtained for ED, NP, DH, and GG with retention time of 3.272 min, 4.098 min, 5.467 min, and 6.783 min, respectively. Good regression coefficient values were obtained in the range of 2–12 μg/ml for ED, 3.75–22.5 μg/ml for NP, 3.125–18.75 μg/ml for DH, and 25–150 μg/ml for GG. The quantification limits were 0.181 μg/ml, 0.187 μg/ml, 0.246 μg/ml, and 1.114 μg/ml for ED, NP, DH, and GG, respectively. The values of validation parameters are within the acceptance limits given by ICH. The ED, NP, DH, and GG showed more percent of degradation in acid condition and less percent of degradation in the neutral condition. The peaks of degradants did not interfere with the peaks of analytes. ED, NP, DH, and GG were assessed with a good percentage of the assay (near to 100%) and low percent relative standard deviation (<2%) in Noscof tablets using the proposed method. Conclusion: The stability indicating RP-HPLC method developed was suitable for quantifying ED, NP, DH, and GG simultaneously in bulk as well as in tablet formulation.